P01.150 hypermutations in glioblastoma are associated with increased response to immunotherapy. (19th September 2018) - Anghileri, E; Zhao, J; Eoli, M; Langella, T; Pollo, B; Indraccolo, S; Pellegatta, S; Iavarone, A; Rabadan, R; Finocchiaro, G
Abstract: Background: Glioblastomas (GBM) exhibit a hyper mutable phenotype only in a restricted subset harboring somatic or germinal mutations of mismatch-repair (MMR) genes. Immunotherapy (IT), including dendritic cell (DC) vaccination and inhibition of immune checkpoints, are actively pursued in GBM patients. We report on two recurrent GBM (rGBM) treated with DC or the anti-PD1 nivolumab. Material and Methods: Whole exome sequencing (WES) was performed on total DNA obtained from peripheral blood and FFPE samples. MMR gene expression evaluated by immunohistochemistry (IHC). Results: Patient MA had first surgery for a grade II astrocytoma when 26. Six years later she had a second surgery diagnosed as methylated MGMT, IDH1-mutated GBM. After six years rGBM was removed and IT with DC loaded with whole tumor lysate was started. 25 months later, MA died for further rGBM. Patient FR, with family history of gastric and uterine cancers in first-degree relatives, was diagnosed with GBM when 33 and treated as standard of care. Sixteen months later, she had second surgery for rGBM, and was treated with nivolumab, still ongoing after 42 months, with no sign of progression. During the treatment she had surgery for a colon adenoma with high-grade dysplasia. We performed WES on peripheral blood and on rGBM tissue of these patients. In MA 6, 900 somatic mutations were detected on rGBM, including two mutations causing sequence changes in the MMR genes MLH3 (T942I) and PMS2 (T485K), described as benign on Polyphen-2. Mutation T942I was reported as germline in a patient with endometrial cancer that had loss of heterozygosity of the other allele on 14q23, a region of LOH also in gliomas. In FR the first and second GBM shared 12, 431 sequence changes, 113 specific of the first GBM and 1, 683 of the second, including missense mutations on MSH2 (R359S) and MSH6 (G39E and Q1155R) genes. Loss of MSH6 was confirmed by IHC and Polyphen-2 prediction indicated the mutation MSH6 Q1155R, but not the other two, as pathogenic. Conclusion: We identified a hypermutator phenotype associated to somatic and germinal mutations of MMR genes in one secondary and one primary GBM, respectively. These patients showed clinical response to IT with prolonged survival. These observations support the idea that in gliomas an increased mutational burden is associated to response to IT and encourage the identification of markers to identify these responsive patients.